Emerging economy MNEs : exploring the integration of knowledge transfer and strategy for sustainable performance - Ogendo, Joan Lilian (Palgrave Macmillan, 2017)
This book explores the influence of the modes of knowledge transfer and environmental dynamism on the relationship between strategic actions and the sustainable balanced scorecard measurement of performance. Special emphasis is placed on emerging multinational enterprises in Kenya, a country that is rapidly becoming one of the fastest growing economies in Africa. The chapters address the best strategy for sustainable performance, the integral modes of knowledge transfer on strategy for sustainable performance and the achievement of sustainable performance in dynamic business environments. Providing innovative research on 25 diverse MNEs in Kenya, this book can be used by managers, investors, consultants, researchers and postgraduate students to understand the strategic mechanisms used by these emerging enterprises.
Keywords: International business enterprises -- Developing countries.; Developing countries.; elektronické knihy; electronic books